Captain's duty : Somali pirates, Navy Seals, and dangerous days at sea / Somali pirates, Navy Seals, and dangerous days at sea - Phillips, Richard, 1956-; Talty, Stephan (New York : Hyperion, 2010)
Tells the dramatic life-and-death tale of the Vermont native who, in April of 2009, was held captive on a tiny lifeboat off Somalia's anarchic, gun-plagued shores.
10 days -- 8 days -- 7 days -- 6 days -- 3 days -- 2 days -- 1 day -- Day 1, 0600 hours -- Day 1, 0735 hours -- Day 1, 0900 hours -- Day 1, 1100 hours -- Day 1, 1530 hours -- Day 1, 1900 hours -- Day 3, 0200 hours -- Day 3, 1800 hours -- Day 3, 1900 hours -- Day 5, 0300 hours -- Day 5, 1945 hours.
Keywords: Phillips, Richard, -- 1956-; Phillips, Richard, -- 1956-; Maersk Alabama (Ship); Maersk Alabama (Ship); Hijacking of ships -- Aden, Gulf of; Merchant mariners -- United States -- Biography; Ship captains -- United States -- Biography; Hijacking of ships -- Gulf of Aden; Merchant marine -- United States -- Biography